2019
DOI: 10.1097/ceh.0000000000000243
|View full text |Cite
|
Sign up to set email alerts
|

Adoption and Use of Mobile Learning in Continuing Professional Development by Health and Human Services Professionals

Abstract: Introduction: Health and human services professionals are increasingly using mobile devices to support clinical decision-making and evidence-based practice. However, research on self-directed learning in an era of growing digital technology utilization is underdeveloped. This study explored the adoption and use of mobile learning as a continuing professional development (CPD) activity. Methods: A mixed-methods case study using semistructured interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 45 publications
1
22
0
3
Order By: Relevance
“…The participants in this study felt that others would assume their smartphone was for personal use. This finding is in line with a recent survey of physicians, nurses, pharmacists, and social workers ( 28 ) that found that “the perception of professionalism” was an important theme and that if the healthcare professional wanted to use their smartphone to access information, it would need to be out of view of colleagues and patients.…”
Section: Discussionsupporting
confidence: 88%
“…The participants in this study felt that others would assume their smartphone was for personal use. This finding is in line with a recent survey of physicians, nurses, pharmacists, and social workers ( 28 ) that found that “the perception of professionalism” was an important theme and that if the healthcare professional wanted to use their smartphone to access information, it would need to be out of view of colleagues and patients.…”
Section: Discussionsupporting
confidence: 88%
“…[3] As NP need to make confident and competent decisions to provide safe and quality care to patients, [4] CPD is essential to meet professional learners needs. [5] Admittedly, mobile devices have become a normalised practice to enhance learning and job referencing [6] to continue professional development. [5] As growing research explores learning beyond the classroom, mLearning is on the rise [7] owing to user independence, [8] flexibility, availability and enhancing motivation to learn.…”
Section: Introductionmentioning
confidence: 99%
“… 10 2019 Lead users of business mobile services International Journal of Information Management Hallikainen, H., Alamäki, A., Laukkanen, T. 11 2019 Value and Barriers to Use of the SIMPL Tool for Resident Feedback Journal of Surgical Education Eaton, M., Scully, R., Schuller, M., (…), Fryer, J.P., Meyerson, S.L. 12 2019 The reasons why elderly mobile users adopt ubiquitous mobile social service Computers in Human Behavior Yang, H.-L., Lin, S.-L. 13 2019 Adoption and Use of Mobile Learning in Continuing Professional Development by Health and Human Services Professionals Journal of Continuing Education in the Health Professions Curran, V., Fleet, L., Simmons, K., (…), Garmsiri, M., Wetsch, L. 14 2019 Drivers and outcomes of branded mobile app usage intention Journal of Product and Brand Management Stocchi, L., Michaelidou, N., Micevski, M. 15 2019 A study on factors influencing the adoption of a crowdsourcing mobile application among generation Y and Z in Maldives International Journal of Recent Technology and Engineering Ali, M.M., Maideen, M.B.H. 16 2020 Factors Affecting Consumer Adoption of Mobile Apps in NCR: A Qualitative Study Global Business Review Arora, N., Malik, G., Chawla, D. 17 2019 Viral marketing and purchase intentions of mobile applications users International Journal of Emerging Markets Fard, M.H., Marvi, R. 18 2019 …”
Section: Methodsmentioning
confidence: 99%